Core-shell structured hyaluronic acid and keratin nanofibers for wound dressing - (:unkn) unknown (IEEE, 2019)
Electrospinning is a one-step, cost-effective and versatile technique that is used at the production of nanofibers from a wide range of biopolymer materials. The high surface area of ultra-thin fibers was produced by electrospinning makes them ideally suitable for various biomedical applications. In this study, keratin and hyaluronic acid as bioactive substances were produced by extracting from animal sources and characterized. The core-shell structured nanofibers were produced by emulsion electrospinning technique with using keratin, hyaluronic acid, polycaprolactone and polyethylene oxide. The morphology, chemical bonding structures, thermal behaviour and mechanical strength of all nanofibers which were produced by adding keratin and hyaluronic acid to these structures separately and together, were investigated.
Keywords: Electrospinning; hyaluronic acid; keratin; wound dressing; biomaterials; DRUG-DELIVERY; ELECTROSPUN